Efficacy and safety of polyethylene glycol loxenatide in treating mild-to-moderate diabetic kidney disease in type 2 diabetes patients: a randomized, open-label, clinical trial - Cao, YongSheng; Cao, Shujie; Zhao, Jiangang; Zhao, Jianqin; Zhao, Yanan; Liu, Ying (Frontiers in Endocrinology, 2024)
Objective This study aimed to evaluate the efficacy and safety of polyethylene glycol loxenatide (PEG-Loxe) compared to those of dapagliflozin in patients with mild-to-moderate diabetic kidney disease (DKD), a prevalent microvascular complication of type 2 diabetes mellitus (T2DM). The study is set against the backdrop of increasing global diabetes incidence and the need for effective DKD management. Methods This study constituted a single-center, randomized, open-label, clinical trial. The trial included patients with mild-to-moderate DKD and suboptimal glycemic control. Eligible participants were randomly allocated to one of the two groups for treatment with either PEG-Loxe or dapagliflozin. The primary endpoint was the change in UACR from baseline at 24 weeks. Results Overall, 106 patients were randomized and 80 patients completed the study. Following 24 weeks of treatment, the PEG-Loxe group exhibited a mean percent change in baseline UACR of −29.3% (95% confidence interval [CI]: −34.8, −23.7), compared to that of −31.8% in the dapagliflozin group (95% CI: −34.8, −23.7). Both PEG-Loxe and dapagliflozin showed similar efficacy in reducing UACR, with no significant difference between the groups (p = 0.336). The HbA1c levels decreased by −1.30% (95% CI: −1.43, −1.18) in the PEG-Loxe group and by −1.29% (95% CI: −1.42, −1.17) in the dapagliflozin group (p = 0.905). The TG levels decreased by −0.56 mmol/L (95% CI: −0.71, −0.42) in the PEG-Loxe group and −0.33 mmol/L (95% CI: −0.48, −0.19) in the dapagliflozin group (p = 0.023). Differences in TC, HDL-C, LDL-C, SBP, and DBP levels between the groups were not statistically significant (all p > 0.05). Safety profiles were consistent with previous findings, with gastrointestinal adverse events being more common in the PEG-Loxe group. Conclusions PEG-Loxe is as effective as dapagliflozin in improving urine protein levels in patients with mild-to-moderate DKD and offers superior benefits in improving lipid profiles. These findings support the use of PEG-Loxe in DKD management, contributing to evidence-based treatment options. Clinical Trial Registration www.chictr.org.cn, identifier ChiCTR2300070919.